1992
DOI: 10.1083/jcb.119.3.629
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor is a potent angiogenic factor which stimulates endothelial cell motility and growth.

Abstract: Abstract. Hepatocyte Growth Factor (HGF, also known as Scatter Factor) is a powerful mitogen or motility factor in different cells, acting through the tyrosine kinase receptor encoded by the MET protooncogene. Endothelial cells express the MET gene and expose at the cell surface the mature protein (p190 MEt) made of a 50 kD (o0 subunit disulfide linked to a 145-kD (~) subunit. HGF binding to endothelial ceils identifies two sites with different affinities. The higher affinity binding site (Kd = 0.35 nM) corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
720
3
3

Year Published

1996
1996
2001
2001

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,252 publications
(741 citation statements)
references
References 69 publications
15
720
3
3
Order By: Relevance
“…Since previous (Paciucci et al, 1998) and our present results showed that production of HGF in pancreatic cancer cell lines is either undetectable or is low and that HGF mediated fibroblast-dependent invasion of pancreatic cancer cells, HGF is likely to be a stromal mediator which affects invasion and probably subsequent metastasis and dissemination of pancreatic cancer cells. Taken together with the notion that HGF is a potent inducer of angiogenesis (Bussolino et al, 1992;Van Belle et al, 1998;Morishita et al, 1999), the abrogation of functional association between HGF and the Met/HGF receptor would be considerable to suppress malignant behaviour of human pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since previous (Paciucci et al, 1998) and our present results showed that production of HGF in pancreatic cancer cell lines is either undetectable or is low and that HGF mediated fibroblast-dependent invasion of pancreatic cancer cells, HGF is likely to be a stromal mediator which affects invasion and probably subsequent metastasis and dissemination of pancreatic cancer cells. Taken together with the notion that HGF is a potent inducer of angiogenesis (Bussolino et al, 1992;Van Belle et al, 1998;Morishita et al, 1999), the abrogation of functional association between HGF and the Met/HGF receptor would be considerable to suppress malignant behaviour of human pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another important aspect of cancer growth and metastasis is the establishment of neovasculature by angiogenesis (Blood et al, 1990). By inducing endothelial cell proliferation and motility, HGF can stimulate neovascularization in vivo (Bussolino et al, 1992;Grant et al, 1993). These findings suggest that HGF, apart from increasing the invasiveness of cancer cells, may also stimulate primary and secondary tumour growth by modulating the tumour matrix (Jiang et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…HGF/SF is a cytokine with unique properties (exerting multiple functions), such as mitogenic and motogenic effects on a variety of normal and transformed cells, and angiogenic (Bussolino et al, 1992;Grant et al, 1993) and morphogenic activity (Montesano et al, 1991). These diverse activities are mediated via a single receptor encoded by the c-MET protooncogene (Naldini et al, 1991;Weidner et al, 1993) al., 1986).…”
Section: Discussionmentioning
confidence: 99%